BEYOND ALLIANCE FOR KNOWLEDGE – STRONGER TOGETHER - Mikkelsen, Harald (Revista Prâksis, 2019)
The Beyond Alliance for Knowledge between Hämeenlinna University of Applied Science, Feevale University and VIA University College is a strategic partnership between three institutions of higher education focused on applied sciences. The alliance was founded in 2017 based on the intention of cooperation in ways in which 1 + 1 + 1 equals more than three. In a world of full of global challenges, it is important to us at VIA, as well as to our partners, to go beyond what each of us can do alone. From my chair as Rector of VIA University College, the alliance is of great importance in relation to creating outlook for our academic environments, e.g. in the form of quality assurance, how to conduct research and new concepts. We are a globally oriented institution and being a part of the Beyond Alliance for Knowledge contributes to the internationalisation of our entire organisation. The staff directly involved in projects under the alliance, carry the knowledge and inspiration they gain back into activities and teaching at home – for the benefit of both colleagues and students, as well as VIA as such.